Some Commentary Notes On Law Number 30 Of 2014 Concerning Government Administration - Hendi Setiawan; Muklis Al’anam; Wandri Munif (Universitas Sriwijaya, 2024)
The position of administrative law in Indonesia does not have a special place compared to other fields of law. This is an important problem, that administrative law does not have a standard codification of general administrative law, like criminal law which has the Criminal Code and civil law which has the Civil Code. The last few decades have been very interesting regarding the contrast in Law Number 30 of 2014 concerning Government Administration which is believed to be material law in the State Administrative Court. The debate about this rule is related to the conflict of norms between articles and other articles in it, according to the author that the rule is a manifestation of the concept of government management and not the rules of general administrative law. So this research needs to be studied through normative legal research methods with a statutory approach and conceptual approach. The results show that there are conflicts of norms and conflicts of rules. Therefore, it is not feasible for this rule to become material law regarding the State Administrative Court. The position of administrative law in Indonesia does not have a special place compared to other fields of law. This is an important problem, that administrative law does not have a standard codification of general administrative law, like criminal law which has the Criminal Code and civil law which has the Civil Code. The last few decades have been very interesting regarding the contrast in Law Number 30 of 2014 concerning Government Administration which is believed to be material law in the State Administrative Court. The debate about this rule is related to the conflict of norms between articles and other articles in it, according to the author that the rule is a manifestation of the concept of government management and not the rules of general administrative law. So this research needs to be studied through normative legal research methods with a statutory approach and conceptual approach. The results show that there are conflicts of norms and conflicts of rules. Therefore, it is not feasible for thisrule to become material law regarding the State Administrative Court.